2017
DOI: 10.1504/ijlc.2017.10001501
|View full text |Cite
|
Sign up to set email alerts
|

Internet Banking Adoption: Case of Lithuania and Latvia

Abstract: Abstract:The banking sector has developed and extended usage of different services at a distance using the internet in the last decade. Internet-based banking services dominate over other historically provided alternatives. This paper explores the adoption of internet banking in Lithuania and Latvia. Internet banking success model was developed based on four main factorsease of use, perceived risk, trust, and perceived usefulness. A survey of Lithuanian and Latvian respondents was carried out. Correlation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Other works such as [34] have shown via Regression results that trust and privacy are the most critical factors influencing e-banking service quality perceptions of customers. Unlike other research studies, the author in [35] analyzed risk and system design as the major dimensions that define customer satisfaction towards ebanking services. Based on the location-specific study, the author in [36] suggested individual behavior tracking as the major contributor to customer satisfaction towards e-banking services.…”
Section: A Literature Depiction Of Individual Behavior Toward Custome...mentioning
confidence: 99%
“…Other works such as [34] have shown via Regression results that trust and privacy are the most critical factors influencing e-banking service quality perceptions of customers. Unlike other research studies, the author in [35] analyzed risk and system design as the major dimensions that define customer satisfaction towards ebanking services. Based on the location-specific study, the author in [36] suggested individual behavior tracking as the major contributor to customer satisfaction towards e-banking services.…”
Section: A Literature Depiction Of Individual Behavior Toward Custome...mentioning
confidence: 99%